ASSESSING THE CREDIBILITY OF ACADEMIC SOURCES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article discusses the critical process of assessing the credibility of academic sources, providing a comprehensive guide for researchers and students. It highlights key factors such as authorship and credentials, the peer review process, publication outlets, citations, bias, methodology, and the overall reputation of sources. The article emphasizes the importance of verifying the expertise of authors, ensuring transparency in research methods, and identifying potential biases to determine whether a source can be trusted. Additionally, it stresses the role of academic community recognition, such as citations and reviews, in confirming a source's reliability.By following the strategies outlined in the article, readers can strengthen their research and ensure the integrity of their academic work.